2005
DOI: 10.1002/nme.1543
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis around holes or notches by special finite elements

Abstract: SUMMARYIn this paper, three special elements for stress concentration analysis around holes or notches are presented. One is based on a variational principle involving displacements, unsymmetric stresses and rotations as independent variables, the other two on the classical Hellinger-Reissner principle. The new elements are designed to be used in a single layer along the cavity rim, where enhanced properties are needed to get a satisfactory level of accuracy. Special properties are obtained by enforcing the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although according to Kirsch [2], the stress concentration factor Kt is 2.64 for a through hole. Stefano de Miranda and Francesco Ubertini [3] analyzed the stress around a hole by finite element simulation and found that their new elements are designed to be used in a single layer along the cavity rim, where enhanced properties are needed to get a satisfactory level of accuracy. However, the limitation acquired sample gives the difficult application due to the lack actual geometry of the parts.…”
Section: Introductionmentioning
confidence: 99%
“…Although according to Kirsch [2], the stress concentration factor Kt is 2.64 for a through hole. Stefano de Miranda and Francesco Ubertini [3] analyzed the stress around a hole by finite element simulation and found that their new elements are designed to be used in a single layer along the cavity rim, where enhanced properties are needed to get a satisfactory level of accuracy. However, the limitation acquired sample gives the difficult application due to the lack actual geometry of the parts.…”
Section: Introductionmentioning
confidence: 99%